Pengaruh Jenis Kelamin dalam Pengetahuan Gizi dan Gaya Makan Eksternal terhadap Pilihan Makanan Sehat pada Mahasiswa: The Influence of Gender on College Students’ Nutrition Knowledge and External Eating Style toward Healthy Food Choices - Azka, Nur Millati; Undarwati, Anna (Amerta Nutrition, 2025)
Background: In Indonesia, the prevalence of obesity remains on the rise, with 35.4% of the population experiencing it. Consuming unhealthy food is one of the influential causes, typically affected by nutritional knowledge and external eating style. Objectives: This study aimed to investigate whether gender, nutrition knowledge, and external eating style influence healthy food choice. Methods: The Behavioral measurement research with quasi experimental design were adopted, recruiting 123 participants selected purposively. The study was conducted in a psychology laboratory using the Fake Food Buffet (FFB) instrument for food choices, the Nutrition Knowledge Questionnaire (NKQ) scale for nutritional knowledge and the Dutch Eating Behavior Questionnaire (DEBQ) scale for external eating styles. The data collected were then analyzed using a generalized linear model. Results: Approximately 61.8% of the participants have a normal Body Mass Index (BMI). Gender and nutrition knowledge showed a negative relationship with healthy food choices (p-value = 0.043; η2 = 0.035). Females having good nutrition knowledge tend to make less healthy food choices compared to males. Additionally, the interaction between gender, nutrition knowledge, and external eating style shows a positive correlation with healthy food choices (p-value = 0.036; η2 = 0.038). Females are more likely to choose healthy food compared to males. Conclusions: The results implied that nutrition knowledge and external eating style influence students’ healthy food choices. Gender may affect consistency in making healthy food choices among students’ eating behavior. Therefore, future research might have further observation on people’s eating behavior.